Research for improved teaching in Kogi State, Nigeria (2007)
In this paper, the issue of whether or not the involvement of the teacher in researching could improve his/her teaching and the subsequent student learning in Kogi state was addresses. In doing this, the state was clustered into three zones in tandem with the existing senatorial district of Kogi East, Kogi Central and Kogi West, while five schools were randomly selected from each zone as well as twenty-five teachers were randomly selected from each of the schools for the descriptive survey part of the study and two sets of sample of thirty teachers each were again randomly chosen the pre-test- post-test experimental/control design. three sets of instrument were used to gather the dataa. Data from the exercise were variously analysed using percentages, means, standard devaition, and t-test. The results show that though reseaching make the teacher to do his teaching, it was also discovered that reseaching improves teaching and learning, funding, lack of training in research, and lask of encouragement had in hibited teacher researching among others. Recommendations included adequate reseach funding for teachers, provision of training in research for teachers and encoraging teachers to do reseach on a consistent and continuous basis for all teachers.